Identification of Two m6A Readers YTHDF1 and IGF2BP2 as Immune Biomarkers in Head and Neck Squamous Cell Carcinoma - Li, Shaojie; Wu, Qiuji; Liu, Jia; Zhong, Yahua (Frontiers in Genetics, 2022)
Abstract Background N6-methyladenosine (m6A) is the most abundant internal modification pattern in mammals that plays critical roles in tumorigenesis and immune regulations. However, the effect of m6A modification on head and neck squamous cell carcinoma (HNSCC) has not been clearly studied. Methods We screened m6A regulators that were significantly correlated with tumor immune status indicated by ImmuneScore using The Cancer Genome Atlas (TCGA) dataset, and obtained distinct patient clusters based the expression of these m6A regulators with the R package “CensusClusterPlus”. We then performed gene set enrichment analysis (GSEA), CIBERSORT and single sample (ssGSEA) to assess the differences of gene function enrichment and tumor immune microenvironment (TIME) among these clusters. We further conducted differently expressed gene (DEG) analysis, weighted gene co-expression network analysis (WGCNA) and constructed protein-protein interaction (PPI) network to determine hub genes among these clusters. Finally, we used the GSE65858 dataset as external validation cohort to confirm the immune profiles related to the expression of m6A regulators. Results Two m6A readers, YTHDF1 and IGF2BP2, were found to be significantly associated with distinct immune status in HNSCC. Accordingly, patients were divided into two clusters with Cluster 1 showing high expression of YTHDF1 and IGF2BP2, and Cluster 2 showing low expression level of both genes. Clinicopathologically, patients from Cluster 1 had more advanced T stage and pathological grade than those from Cluster 2. GSEA showed that Cluster 1 was closely related to RNA modification process and Cluster 2 was significantly correlated with immune regulations. Cluster 2 had a more active TIME characterized by more relative abundance of CD8+ T cell and CD4+ T cell and higher levels of MHC I and MHC II molecule. We constructed a PPI network composed of 16 hub genes between the two clusters, which participated in T cell receptor signaling pathway. These results were externally validated in the GSE65858 dataset. Conclusions The m6A readers YTHDF1 and IGF2BP2 were potential immune biomarkers in HNSCC and could be potential treatment targets for cancer immunotherapy.